Soil Erosion Estimation Using Geospatial Technology: A Study of Jyadul Khola Basin, Gorkha, Nepal - Adhikari, Sandeep; Shrestha, Prabesh; Ghimire, Motilal (The Geographic Base, 2022)
Estimation of soil erosion from drainage basins is essential while assessing the severity and its impact on agriculture, forests, barren land, waterbodies, and built- up areas. Jyadul Khola basin significantly affects the ecological processes that feed into the Budhigandaki River in the south-eastern side of Gorkha District. This paper has attempted to estimate the mean erosion rate based on the erosion severity classes. Remotely sensed Ziyuan-3 satellite image processed in Earth Resources Data Analysis System (ERDAS) Imagine, Geographical Information System (GIS), and Revised Universal Soil Loss Equation (RUSLE) model were used in this study. The land use land cover (LULC) classification results were validated by using confusion matrix by computing overall accuracy and kappa coefficient which is 95% and 0.94 respectively. The basin had been classified into 6 categories based on erosion severity. The results indicated 92.7% of land (0-5 t ha–1 yr–1) is low severe followed by 2.39% (10-20 t ha–1 yr–1) moderate, 2.07% (5-10 t ha–1 yr–1) high, 2.04% (20-40 t ha–1 yr–1) very high, 0.67% (40-80 t ha–1 yr–1) severe and 0.10% of land (>80 t ha–1 yr–1) which is very severe for soil erosion. The total annual mean soil loss was found to be 13526.60 t yr–1 and soil erosion classes ranges from 0 to 305.34 t ha–1 yr–1 for the entire study area. Kuwapani, Lakuri Bhanjyang, Khadkagaun, Garapani and Kaulebhagar area are the most susceptible to soil erosion. It is observed that barren land, steep slopes, and high intensity of rainfall are major factors for soil erosion hazard. This outcome can serve as a foundation for decision-makers to conserve high risk areas and plan effective measure to lessen impending disasters.